The translators who shook the world: journalists and translators in the Russian Revolution. - Rodríguez-Espinosa, Marcos (Taylor & Francis, 2022)
Shortly after the outbreak of the Russian Revolution in February 1917, foreign newspapers and news agencies dispatched some of their best journalists, including a group of highly rated women reporters, to send their chronicles from a conflict which left an enduring memory in their lives. Most correspondents who travelled to Russia soon realised that their news coverage would depend on their recruitment of translators, interpreters, or other language mediators. Drawing on a selection of historical, journalistic and translation research sources, as well as on a number of memoirs, personal accounts and biographies of foreign correspondents, in this article we examine a number of unexplored topics related to the complementary and sometimes contradictory relationship between journalists and translators and interpreters during the Russian Revolution: (a) the demanding communication issues faced by foreign correspondents on their arrival in the country; (b) the meaningful contribution, frequently obscured in journalistic accounts, of translators or interpreters in the newsgathering process; (c) the ambivalent relationship between journalists and translators and how their divergent political ideologies might have interfered with their bond of trust; and (d) the role of correspondents within activist networks, especially in the Bolshevik party, when performing propaganda activities, which included diverse translation assignments.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/19878
Keywords: Rusia - Historia - 1917-1921 (Revolución); Periodismo - Traducción; Journalistic translation; History of translation; Translation and conflict; Translation and activism; Russian revolution